Production of Tomato Stalk Biochar and its Usage in Hydrophonic Agriculture - Ceren Karakaş; Didem Özcimen (Journal of Chemical Engineering Research Updates, 2017)
Tomato stalk is a waste remained after harvesting in agricultural productions. These wastes can be utilized as biochar for various purposes such as fuel, absorbent and soil improver. In this study, in order to waste utilization, biochar production from tomato stalk under different experimental conditions was carried out and effect of temperature, nitrogen gas flow and heating rate on yield of biochar was investigated. Characterization of biochar was performed with FTIR, TGA and SEM analysis. The highest biochar yield was obtained at the temperature of 773 K, heating rate of 5 K/min and inert gas flowrate of 500 ml/min. The highest yielded tomato stalk biochar was used as a supporting material for the tomato seedling planted in the hydroponic system of greenhouse. The tomato stalks obtained as a waste after harvesting in greenhouse were used for biochar production and biochars were applied as supporting material in greenhouse again, so, zero waste idea for a greenhouse was carried out. It has been observed that the supporting material provided a little more growth in the tomato seedling because of water and nutrient holding capacity.